2023
DOI: 10.1097/iae.0000000000003726
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Intravascular Catheter-Assisted Sutureless Scleral Fixation of Three-Piece Intraocular Lenses: A Novel Technique

Abstract: To describe and report the anatomical and functional outcomes of a novel sutureless peripheral intravascular catheter (PIVC)-assisted scleral fixation of three-piece IOL.Methods: A retrospective chart review of all patients who underwent scleral fixation surgery performed by a single surgeon was conducted. In all cases, a novel scleral fixation technique of three-piece IOL was performed with the aid of a 24-gauge PIVC cannula. Patients were followed up at postoperative months 1, 3, and 6.Results: Thirteen eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…16,22 A SFIOL technique using 24-g peripheral intravascular catheter was recently described, with no reported IOL dislocations in 6-month follow-up in 13 eyes. 23 Our practice of haptic flanging of PMMA or polyvinylidene fluoride-based haptics represents off-label use of three-piece IOLs. Our study demonstrated a relatively low rate (3.3%) of haptic exposure or erosion in comparison with a recent published report, which used a scleral flap technique as prophylaxis against haptic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…16,22 A SFIOL technique using 24-g peripheral intravascular catheter was recently described, with no reported IOL dislocations in 6-month follow-up in 13 eyes. 23 Our practice of haptic flanging of PMMA or polyvinylidene fluoride-based haptics represents off-label use of three-piece IOLs. Our study demonstrated a relatively low rate (3.3%) of haptic exposure or erosion in comparison with a recent published report, which used a scleral flap technique as prophylaxis against haptic exposure.…”
Section: Discussionmentioning
confidence: 99%